(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In this article the problems that are depend on the function of “ Operative forensic and the section that services to notify the accidents” were discussed. Creating of new normative documents that are mark the activity service and modern methods of scientific organizational work were offered.